ANALYSIS OF SOCIAL COMPETENCY CHARACTER PLANTING IN CURRICULUM 2013 IN ELEMENTARY SCHOOL STUDENTS AT SDN 060870 MEDAN TIMUR SUBDISTRICT IN MEDAN CITY - Novani Maryam Rambe; Deny Setiawan; Siman Siman (Jurnal Ilmiah Teunuleh, 2020)
Abstract This study aims to study social competency character growers in elementary school 060870 East Medan, analyzing how the planting of social competency characters is influential in elementary school 060870 East Medan. This research uses a qualitative approach with descriptive analysis. The data analyzed were interviews with teachers, students, principals of SDN 060870, observations, and documentation. The results showed that: the planting of social competencies in the 2013 curriculum was carried out well. There are 2 aspects seen in the character of social competence, namely; first, interaction behavior, which has 4 characteristics contained therein; second, communication behavior which has 3 characteristics contained therein. Therefore, it is concluded that the planting of the character of social competence in SDN 060870 is carried out properly and in accordance with the required categories.